PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE BENAR SALAH BERANTAI (TRUE FALSE CHAIN) UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI IPA SMAN 2 BANGKINANG - Aulia Elphalizwani Elphalizwani; Rasmiwetti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to improve students' cognitive learning outcomes onthe subject of chemical equilibrium in class XI IPA SMAN 2 Bangkinang academic year2014/2015 with the application of active learning strategy of True False Chain type.The research is experimental research with pretest-posttest design. There are twoclasses for the sample, XI IPA 1 as an experiment class and XI IPA 4 as control classwhich randomly selected after testing homogeneity. Experimental class is a class that istreated given to the application of active learning True False Chain type. Data analysistechnique used is the test for normality using Liliefors test, homogeneity test and testhypotheses. Hypothesis testing using t test. Based on the research results obtained atlast calculation of data process tcalculed> ttable ie 2.5839> 1.67, which means theapplication of active learning strategy of True False Chain type can improve cognitiveachievement of students on the subject of chemical equilibrium at XI IPA SMAN 2Bangkinang with an increase of 9,187%.Key Words: Active Learning True False Chain Type , Cognitive Learning Outcomes of Students